Implementing the Role of The Ngos in Curricular and Societal PPKn Through Political Literacy in Indonesia - Anjarsari, Riya (RSF Conference Series: Business, Management and Social Sciences, 2023)
The importance of political literacy in improving people’s understanding of political education, citizens’ rights and obligations, and being able to actively participate in the democratic process. In this context, NGOs have the potential to contribute to developing political literacy that is more effective and has a wider impact. Although Civics is an integral part of the curriculum, the challenge of teaching democratic values and effective political participation can still be implemented by NGOs as a form of curricular and societal Civic education. Penguatan Pendidikan Karakter, PPKn (Civic Education) is a Nawa Cita (government program) mandate proclaimed by President Joko Widodo about carrying out a character revolution. Civic education also concerns the personality or morals of students because the current generation is the golden generation who will become leaders in 30 years. The research in this paper aimed to find out the role of NGOs related to political literacy in society through education and advocacy strategies. The research method used was qualitative with data collection techniques of observation, documentation, and structured, open, and in-depth interviews with informants selected by purposive sampling. The findings were based on the results of research conducted for six months from January to June 2023 with limitations in regional coverage. The political literacy program was declared successful in demonstrating the role of NGOs with the strategy of conducting political literacy training, providing easy-to-understand political information, holding public discussions, inviting people to get involved in the political process, and establishing partnerships with government institutions and civil society. Political literacy activities have a positive impact on participants although it is not seen and impacted directly by the entire community. As a conclusion, through political literacy, NGOs can help people become politically literate, less susceptible to political issues, and more open in their political thoughts and actions.